Pemanfaatan Kecerdasan Buatan dalam Diagnostik Medis: Tantangan dan Peluang - Rahmatillah, Zahra (Maliki Interdisciplinary Journal, 2025)
One of the most important medical innovations, especially in diagnostics, is artificial intelligence (AI). This article discusses the use of AI in medical diagnostics, pointing out the advantages, disadvantages, and prospects. AI can improve diagnosis accuracy, speed up the treatment process, and customize patient care quickly and accurately. However, issues such as algorithm validity, data privacy, and the ethical use of this technology should be considered as well. The purpose of this article is to provide an understanding of how AI can change the paradigm of medical diagnostics and provide suggestions for better implementation. In the field of medical diagnostics, artificial intelligence (AI) has created new ways to improve the accuracy and effectiveness of disease diagnosis. the application of AI in medical diagnostics is also faced with a number of challenges. The quality of the data used to train algorithms is crucial, yet medical data is often incomplete, inconsistent and sensitive in nature. Moreover, interpretation of results generated by AI requires in-depth medical expertise to ensure informed decisions. In addition, this article discusses the role of AI in various medical fields, such as medical imaging and genomic data analysis. The article discusses the issues encountered as well as opportunities and challenges, including ethical concerns, data privacy, and technological limitations. This comprehensive analysis is expected to provide insights into how AI can be better utilized in medical practice and the difficulties that exist. Through a comprehensive analysis of various case studies, this research found that AI can improve diagnosis efficiency and accuracy, but also faces challenges such as data quality, algorithm bias, and ethics. Nonetheless, with the rapid development of technology and strong collaboration between medical experts and computer scientists, AI has the potential to be an invaluable tool in improving the quality of healthcare.